Ursolic acid does not change the cytokine levels following resistance training in healthy men: A pilot balanced, double-blind and placebo-controlled clinical trial - Patrícia Cristina Barreto Lobo (Elsevier, 2022)
Ursolic acid (UA) is a natural compound that shows anti-inflammatory actions. However, no human studies have investigated the cytokine profile during the RT and UA consumption. The purpose of this study was to verify if UA is able to potentiate the anti-inflammatory activity after RT, reflecting in the reduction of blood inflammatory markers in healthy men. Twenty-seven participants were allocated to two groups: control (CON) (n = 13) and UA (n = 14). For 8weeks, each group performed RT and consumed capsules containing a placebo (400 mg/day) or UA (400 mg/day). Serum cytokine concentrations were evaluated before and after the training period. There was no difference in the serum cytokine concentrations of TNF-α, IL-10 and IL-6 (p > 0.05). In conclusion, UA supplementation for 8weeks was not able to change the blood TNF-α, IL-10, and IL-6 concentrations in healthy men undergoing RT. However, further studies are warranted to investigate other inflammatory markers.